Transactions of mobility: Community trade centre to promote job security and networking in Phokeng - Belisha, Edan (University of the Witwatersrand, Johannesburg, 2024)
This architectural thesis is an in-depth study of local space-making with the aim of enhancing local networking and economic growth within the Phokeng community. The research is community-led and focuses on local services and spaces, as a way in which to incorporate rituals of everyday life. Through careful analysis of the community's spatial dynamics, a central hub arranged around a transport interchange is developed and proposed. Phokeng possesses the potential for prosperity due to the community’s distinctive Bafokeng identity and resources derived from their fertile and platinum rich landscapes. However, the community is socially and geographically isolated from local and global networks. Local individuals see these limitations to networking, unreliable access to local services and limited opportunities to develop experience and skills as the primary barriers to finding employment. Against this backdrop, the study focuses on three crucial areas: identity, transactions, and interactions. Through an in-depth examination of these areas, the study is aimed at creating a central hub for the Phokeng community to network and facilitate job security. This central hub becomes a strategic solution to foster collaboration and promote growth within the Phokeng community, with the potential of this hub serving as a springboard for wider development within the Bakofeng region.
A research report proposal submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Architecture (Professional).
Keywords: Phokeng community; Bafokeng; Identity; Transactions; Interactions; Local networking; Economic growth; SDG-11: Sustainable cities and communities